Development of an Actuator for Translatory Movement by Means of a Detented Switching Shaft Based on a Shape Memory Alloy Wire for Repeatable Mechanical Positioning - Tobias Schmelter; Benedict Theren; Sebastian Fuchs; Bernd Kuhlenkötter (Crystals, 2021)
Actuators based on the shape memory effect have recently become more and more economically important due to the many advantages of shape memory alloys (SMAs), such as their high energy density. SMAs are usually used to control the end/maximum positions, thus the actuators always move between two positions. The repeatable control of intermediate positions has so far proven difficult, because in most cases, external sensors are necessary to determine the length of the SMA element. Additionally control strategies for SMA actuators are rather complex due to the non-linear behavior of this material. The SMA actuator presented here is able to control intermediate positions with repeatable accuracy without the need of a separate control technology. The integrated control unit is based on a mechanical principle using a shaft with a circumference groove. This groove has a height profile that turns the shafts rotation, generated by the SMA, into a translational movement. Therefore, the SMA wire generates a partial stroke at each complete activation, turning the shaft partially. With several activation cycles in a row, the stroke adds up until reaching the maximum. A further activation cycle of the wire resets the actuators stroke to its initial position. Each part of the stroke can, thereby, be controlled precisely and repeatedly within the scope of each complete cycle of the actuator. Based on an integrated ratchet, each stroke of the actuator can hold energy free.